Practitioner research and professional development in education. - Campbell, Anne (Online access: SAGE SAGE Research Methods Core., 2004)
Drawing directly on the work of teachers and other professional trainers concerned with programmes for continuing professional development, Research for Professional Development promotes action research for practitioners so as to develop qualities of critical appraisal and analysis of practice, appropriate to professional contexts.